Development of multiband rectangular shaped parasitic elements (RSPE) planar inverted-f antenna for wireless applications / Fatimah Nur Mohd Redzwan - Mohd Redzwan, Fatimah Nur (2016)
In this project, the multiband PIFAs for wireless applications were designed and constructed, which were Single-Band PIFA (SB-PIFA), Dual-Band PIFA (DB-PIFA) with one rectangular-shaped parasitic element, and Triple Band PIFA (TB-PIFA) with the introduction of two rectangular-shaped parasitic elements that were placed under the main radiating patch of the PIFA in order to obtain a triple-band operation. The size of ground plane of the proposed PIFA is 50 x 30 mm which has been reduced by 50% from the size of conventional PIFA. This can be achieved by adjusting the width and the height of shorting plate. The SB-PIFA operates at 2.6 GHz for LTE Application. In DB-PIFA, two frequency spectrums operating at 2.6 GHz and 3.5 GHz frequency band for LTE and WiMAX application has been proposed. The dual-band operation is obtained after introducing a rectangular shape parasitic element togenerate new resonant frequency at 3.5 GHz. The best location of parasitic element is placed on the right edge of the ground plane due to the existing of high current distribution. Meanwhile, the third design TB-PIFA operating at 2.1 GHz for UMTS2100, 2.6 GHz (LTE) and 3.5 GHz (WiMAX) frequency band is presented. This design adopted the same technique as the DB-PIFA to generate triple-band frequencies, where one more parasitic element is added and placed at the left edge of the ground plane. In TB-PIFA, the main radiating patch controlled the upper band frequency at 3500 MHz, while the first parasitic element excited at the middle band frequency (2600 MHz), and the second parasitic element contributed to lower band frequency at 2100 MHz. Besides, this parasitic element technique also useful for bandwidth enhancement and increase the antenna gain. These multiband antennas have a simple mechanical construction and could be a good candidate to be used as mountable antenna in mobile devices. In these frequency bands, the antennas gave nearly omni-directional radiation pattern with the peak gained between 2 dBi to 5 dBi and measured antenna efficiencies from 40% to 70%.